PERANCANGAN SISTEM AIR SUSPENSION PADA SEPEDA MOTOR HONDA VARIO 110 - Hidayat, Ramdan; Akmal Islami, Lazuardi; Sumarno, Dodi Iwan (Universitas Nusa Putra, 2022)
This study discusses the suspension on motorcycles by changing the standard suspension system, namely spring suspension / Coil Spring by designing an air suspension system to be applied to the Honda Vario 110 motorcycle. There are several problems with the suspension of spring-type motorcycles, namely when adjusting the suspension and the level of comfort. The purpose of this study is toknow the construction design, design and know the ratio of damping values pthere is an air suspension system and coil spring applied to the initial design of the motorcycle. The design and simulation method carried out is using Autodesk Inventor 2020 Software. In this design process, there are additions to the construction, namely the holder for the suspension as an air suspension support and changes to the size of the engine mounting which is extended to increase the suspension water storage space. As a result of the Autodesk Inventor 2020 simulation, the Air Suspension made of rubber with a load of 300 kg with a damping value of 7,744 N/m is greater than the initial suspension made of steel wire spring (SW) with a value of 7,500 N/m.